Práticas de letramento de alunos do terceiro ano do ensino fundamental I do entorno de Brasília com dificuldades de aprendizagem em leitura e escrita - (:unkn) unknown (Universidade Federal de Goiás, 2020)
The purpose of this research proposal was to understand the literacy practices of third year elementary school students with learning difficulties in reading and writing. Qualitative ethnographic research was used for this study. The term literacy emerged in Brazil in the mid1980s and since then its real meaning has been discussed. An individual may not know how to read and write, but in a way he can be literate, as he lives in the midst of reading and writing. The theoretical studies of this work were based on the works of Mary kato (1994), who was the first person to use the term literacy in Portuguese, Leda Verdiani Tfouni (1995 and 2010), Ângela Kleiman (1995) and Magda Soares (1987, 1996, 2004, 2010 and 2016). This research relied on the participation of family members of children with learning difficulties in a public school in the vicinity of Brasilia, the children's reports with the objective of telling the difficulties encountered in the literacy process, and the participation of teachers reporting what the difficulties were that they find and consider difficult to be faced in teaching literacy. The data collection process took place through semi-structured interviews, with children, families and teachers. The meetings were recorded and recorded in a field notebook. The researched houses were photographed in order to show the distance between the school and the researched community. During the interviews with the families, participant observation was carried out. The research revealed a reality of distance between the school and the reality experienced by children outside it, which makes the teaching-learning process difficult. Studies also show that there is a lack of harmony between pedagogical actions and the reality experienced by local communities. The practices worked in schools, need to have meaning for the subjects in their daily experiences and practices. The interviews with families, students and teachers made it possible for us to realize that the practice of literacy is still rooted in traditional methods and that many teachers have not appropriated the concept of the term “literacy”.
Third-year student lettering practices of the fundamental education of the environment of Brasília with learning diffi-culties in reading and writing
Keywords: Letramento; Alfabetização; Dificuldade de aprendizagem; Família; Literacy; Learning difficulties; Family; CIENCIAS HUMANAS::EDUCACAO